Export pumps for glutathione S-conjugates - Keppler, Dietrich (Free radical biology and medicine, 1999)
The release of glutathione S-conjugates from cells is an ATP-dependent process mediated by integral membrane glycoproteins belonging to the recently discovered multidrug-resistance protein (MRP) family. Many lipophilic compounds conjugated with glutathione, glucuronate, or sulfate are substrates for export pumps of the MRP family. In humans six MRP isoforms encoded by different genes have been cloned. Orthologs of MRP have been identified in many species including yeast, plants, and nematodes. Human MRP1 and MRP2 are currently best characterized with respect to substrate specificity by measurements of ATP-dependent transport into inside-out membrane vesicles. High-affinity substrates include the glutathione S-conjugate leukotriene C4, S-(2,4dinitrophenyl)glutathione, bilirubin glucuronosides, and 17β-glucuronosyl estradiol. In addition, glutathione disulfide is transported by MRP1 and MRP2. Reduced glutathione may be released from cells in a process directly or indirectly mediated by members of the MRP family. Proteins of the MRP family are indispensable for transport of glutathione S-conjugates and glutathione disulfide into the extracellular space and play, therefore, a decisive role in detoxification and defense against oxidative stress.